REACH MATHEMATICAL CONNECTION ABILITY BY PROBLEM POSING APPROACH - nurlissolihah nurlissolihah; Indri Lastriyani; Rosalina Rolina (IKIP Siliwangi, 2018)
This study aims to examine the mathematical connection ability of students between the learning using problem posing and the scientific approach. The method used in this study is an experimental method with a pretest-posttest control group design involving two groups and random sampling is taken at the beginning, at the beginning and end of learning the two classes are given a test. The population in this study were junior high school students in Bandung, while the sample consisted of two classes chosen randomly. One class is givenlearning problem posing and the other class is given a scientific approach. The instrument used is a set of 5 test questions describing mathematical connection ability, then the score data is analyzed with descriptive and inferential statistics using SPSS Statistics 21. Based on the results of the study, it was concluded that the achievementabilities of students' mathematical connectionbetween learning using problem posing was better than students who used a scientific approach.